The Stabilizing Role of the Compensatory Financing Facility : Empirical Evidence and Welfare Implications. (IMF Working Papers; Working Paper, 1988)
Purchases under the compensatory financing facility, the IMF's largest special facility, accounted for more than one quarter of total credit extended by the IMF over the period 1976 to 1985. Given the size of these operations, it is of some interest to determine to what extent the facility served its intended purpose-the stabilization of foreign exchange earnings of member countries experiencing temporary export shortfalls. This paper develops a methodology for evaluating the CFF's stabilizing role and provides some quantitative evidence of its effectiveness. This evidence is then used to obtain an indication of the facility's role in stabilizing the demand for international reserves and its contribution to net welfare gain. The results suggest that the facility has been important in stabilizing members' earnings, and that the net benefits derived by them can be regarded as substantial.